Deliberative democracy in health care: current challenges and future prospects - Safaei J (Dove Medical Press, 2015)
Jalil Safaei Department of Economics, University of Northern British Columbia, Prince George, BC, CanadaBackground: There is a vast body of literature on deliberative, participative, or engaged democracy. In the area of health care there is a rapidly expanding literature on deliberative democracy as embodied in various notions of public engagement, shared decision-making (SDM), patient-centered care, and patient/care provider autonomy over the past few decades. It is useful to review such literature to get a sense of the challenges and prospects of introducing deliberative democracy in health care.Objective: This paper reviews the key literature on deliberative democracy and SDM in health care settings with a focus on identifying the main challenges of promoting this approach in health care, and recognizing its progress so far for mapping out its future prospects in the context of advanced countries.Method: Several databases were searched to identify the literature pertinent to the subject of this study. A total of 56 key studies in English were identified and reviewed carefully for indications and evidence of challenges and/or promising avenues of promoting deliberative democracy in health care.Results: Time pressure, lack of financial motivation, entrenched professional interests, informational imbalance, practical feasibility, cost, diversity of decisions, and contextual factors are noted as the main challenges. As for the prospects, greater clarity on conception of public engagement and policy objectives, real commitment of the authorities to public input, documenting evidence of the effectiveness of public involvement, development of patient decision supports, training of health professionals in SDM, and use of multiple and flexible methods of engagement leadership suited to specific contexts are the main findings in the reviewed literature.Conclusion: Seeking deliberative democracy in health care is both challenging and rewarding. The challenges have been more or less identified. However, its prospects are potentially significant. Such prospects are more likely to materialize if deliberative democracy is pursued more systematically in the broader sociopolitical domains.Keywords: citizen juries, patient engagement, shared decision-making, decision aids, public participation